Identification of Cryptococcus neoformans Isolates by PCR-ITS regions - Aswad, Esraa Muslim; Al-Temimay, Israa A. (Iraqi Journal of Science, 2018)
The aim of the study was molecular detection of C. neoformans that isolated from 150 (88 female and 62 male) clinical samples (sputum samples) from pulmonary patients in Baghdad. The diagnoses of Cryptococcus neoformans in samples was done by using direct microscopic examination, culture media and PCR Technology. Microscopic examination and cultured revealed that 65 out of 150 (43.33 %) samples were positive and the others samples were Negative. Results of the genetic diagnosis looking for the fungi causing cryptococcosis using primers specific for ITS gene which were specially designed for this study revealed that 6 (4 %) of sputum samples were positive. In this study used the PCR technology due to the present of high specificity and sensitivity for the diagnosis of C. neoformans added to that which is cheaper and faster than the conventional methods currently used in hospital and laboratories.